2021
DOI: 10.1111/ans.16663
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder carcinoma outcomes in an Australian tertiary referral hospital

Abstract: Background This study aimed to examine the presentation, treatment, and long‐term outcomes of patients with gallbladder carcinoma (GBC) managed in a surgical unit of an Australian tertiary referral hospital of a 19‐year period. Methods A retrospective review of prospectively collected data of patients with GBC managed in the Royal North Shore Upper GI Surgical department from October 1999 to March 2018. Results A total of 104 patients with GBC were identified: 36 patients underwent palliative treatment, 61 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is substantially better than other worldwide estimates. The 2018 GLOBOCAN data published an estimated worldwide mortality rate of 1.6/100,000 for males and 1.8/100,000 for females (compared to 0.9 [males] and 1.0 [females] in Australia) [ 29 ]. This is likely attributable to the advanced healthcare system in Australia which facilitates early diagnosis, advanced surgical techniques (liver resection and lymph node dissection), and progressive adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is substantially better than other worldwide estimates. The 2018 GLOBOCAN data published an estimated worldwide mortality rate of 1.6/100,000 for males and 1.8/100,000 for females (compared to 0.9 [males] and 1.0 [females] in Australia) [ 29 ]. This is likely attributable to the advanced healthcare system in Australia which facilitates early diagnosis, advanced surgical techniques (liver resection and lymph node dissection), and progressive adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely attributable to the advanced healthcare system in Australia which facilitates early diagnosis, advanced surgical techniques (liver resection and lymph node dissection), and progressive adjuvant therapy. Although survival data were not available for analysis in our study, single institution data from an Australian tertiary referral hospital demonstrated a median survival of 35 months [ 29 ] for GBC patients treated at their center.…”
Section: Discussionmentioning
confidence: 99%
“…Data on patient characteristics, surgical treatment and survival of this cohort has been published elsewhere. 18…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a study in Japan of 200 GB carcinoma patients who underwent surgical resection reported the following 5-year overall survival rates: Stage I, 90.8%; stage IIA, 94.4%; stage IIB, 73.6%; stage IIIA, 33.7%; stage IIIB, 57.7%; stage IVA, 14.3%; and stage IVB, 11.8%[ 88 ]. A study conducted in Australia including 104 patients with GB carcinoma and a median follow-up of 60 mo found a median overall survival of 35 mo in those with intended curative resection and 4 mo in inoperable cases with palliative treatment[ 36 ]. For a T1b follow-up of 69.9 mo, the disease-free survival was 92%[ 50 ].…”
Section: Prognosismentioning
confidence: 99%